A wind turbine nacelle cover integrally formed anti-skid belt and a manufacturing method thereof
Patent Information
- Application Number
- CN202611271069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种风力发电机机舱罩一体成型防滑带及其制造方法,本发明解决的技术问题在于,成型后撒砂工艺中的防滑颗粒仅靠表层胶衣附着,粘结强度低,在长期室外工况下极易脱落,且人工撒砂均匀性难以控制,另一方面,模具成型工艺需单独制作并粘接防滑带模具,工序繁琐、模具易磨损脱落,且脱模剂残留易影响防滑表面的成型质量
1、本发明通过将防滑颗粒嵌于防滑带胶衣层与产品胶衣层之间,并通过树脂浸润玻璃纤维及夹芯材料层后共固化形成一体化复合材料结构,实现了防滑颗粒的上下双重胶衣包覆锚固与材料深度结合,相比传统成型后仅靠表层胶衣附着防滑颗粒的撒砂工艺,提升了防滑层的粘结强度,避免了在长期户外温差循环及人员踩踏工况下的脱落问题,延长了防滑带的使用寿命。
Smart Images

Figure CN122919699A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wind power equipment manufacturing technology, specifically to an integrated anti-slip strip for a wind turbine nacelle cover and its manufacturing method. Background Technology
[0002] During long-term operation, wind turbine generators often require maintenance personnel to climb to the top of the nacelle for equipment inspection and maintenance. To ensure the safety of personnel working at height, an anti-slip structure is usually installed on the top of the nacelle, which is made of composite materials such as fiberglass, to provide reliable anti-slip safety protection.
[0003] Currently, in the wind power manufacturing industry, the anti-slip treatment of the nacelle cover top mainly relies on two traditional processing techniques. The first is the post-molding sand-spreading method. In this process, after the main body of the nacelle cover has completely cured, the surface of the pre-designed anti-slip strip area is sanded and coated with gel coat. Then, before the gel coat has cured, anti-slip particles such as quartz sand are manually spread. This method mainly relies on the mechanical interlocking force of the surface gel coat to fix the anti-slip particles. The anti-slip particles only adhere to the outermost layer of the product, resulting in low overall bonding strength. Under the complex outdoor conditions of wind turbines, such as long-term exposure to wind and sun, cyclical temperature changes, and repeated trampling by maintenance personnel, the anti-slip particles are prone to peeling and falling off, shortening the service life of the anti-slip surface, and the fallen particles also cause environmental pollution. In addition, the manual sand-spreading construction method makes it difficult to accurately control the uniformity of the distribution of anti-slip particles and the overall thickness of the anti-slip layer, resulting in poor consistency in the surface quality and friction performance of the finished products during mass production.
[0004] The second common anti-slip treatment process is the mold forming method. This method requires pre-marking the anti-slip strip area on the main mold of the canopy, then separately fabricating an additional mold with anti-slip texture, and bonding it to the corresponding area of the main mold, so that the canopy surface has an inherent anti-slip structure after demolding. Although this process improves the uniformity of the surface texture to some extent, it requires the additional fabrication and assembly of the anti-slip strip mold, which not only increases mold costs but also makes the entire manufacturing process very cumbersome. Since the additional mold is fixed to the main mold by bonding, the bonded surface is prone to wear and even detachment during repeated production and demolding, making subsequent maintenance and positioning very difficult. On the other hand, since the mold forming method requires the use of a release agent, the residue of the release agent in the dead corners of the anti-slip texture will directly affect the surface molding quality, resulting in unstable exposure of anti-slip particles on the final product surface, making it difficult to maintain the surface roughness and anti-slip effect required by the design. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides an integrated anti-slip strip for wind turbine nacelle covers and its manufacturing method. The technical problem solved by this invention is that the anti-slip particles in the sand-spreading process after molding are only attached by the surface gel coat, resulting in low bonding strength. They are prone to falling off under long-term outdoor conditions, and the uniformity of manual sand spreading is difficult to control. On the other hand, the mold forming process requires the separate fabrication and bonding of the anti-slip strip mold, which is cumbersome, the mold is prone to wear and fall off, and the residue of the release agent can easily affect the molding quality of the anti-slip surface.
[0006] To address the above problems, the present invention provides the following technical solution: The first aspect of the present invention provides an integrally molded anti-slip strip for a wind turbine nacelle, comprising an anti-slip strip gel coat layer, an anti-slip particle layer, a product gel coat layer, and a fiberglass and core material layer; The anti-slip particle layer is composed of a plurality of anti-slip particles spaced apart and is disposed between the anti-slip tape gel coat layer and the product gel coat layer; The anti-slip particles have an exposed end and an anchoring end. The exposed end passes through the anti-slip tape gel coat layer and forms a particle exposed surface that is not continuously covered by the anti-slip tape gel coat layer. The anti-slip tape gel coat layer covers the periphery of the anti-slip particles near the exposed end. The product gel coat layer covers the periphery of the anti-slip particles near the anchoring end and the anchoring end. The glass fiber and core material layer is disposed on the side of the product gel coat layer away from the anti-slip particle layer, and the side of the product gel coat layer away from the anti-slip particle layer forms an interface bond with the cured resin in the glass fiber and core material layer; The exposed surface of the particles together with the gel coat layer of the anti-slip tape form an anti-slip surface.
[0007] Furthermore, the exposed end of the anti-slip particles, their surface, sharp corners, or edges, together with the gel coat layer of the anti-slip tape, form a granular, rough anti-slip texture. The anti-slip particles are quartz sand, corundum sand, silicon carbide particles, or ceramic particles.
[0008] A second aspect of the present invention provides a method for manufacturing an integrally molded anti-slip strip for a wind turbine nacelle, comprising the following steps: Define an anti-slip strip area on the mold surface, process grooves within the anti-slip strip area, clean the mold surface, and apply a release agent; Spray anti-slip gel coat into the groove of the mold, and let it stand until it is surface dry and not completely cured, forming an anti-slip gel coat layer. Anti-slip particles are laid on the surface of the anti-slip tape gel coat layer. The end of the anti-slip particles facing the mold is the exposed end, and the end of the anti-slip particles away from the mold is the anchoring end. The exposed ends of multiple anti-slip particles are pressed into the anti-slip tape gel coat layer until they contact the bottom surface of the groove, forming an anti-slip particle layer. Spray product gel coat onto the entire surface of the mold, so that the product gel coat covers the periphery of the anti-slip particles near the anchor end and the anchor end, and fills the gap between adjacent anti-slip particles near the anchor end, and let it stand until it is surface dry to form a product gel coat layer. Fiberglass material and core material are laid on the surface of the product gel coat layer. During or after the laying of the fiberglass material, resin is impregnated into the fiberglass material to form a fiberglass and core material layer. Subsequently, curing is performed to form an interface between the cured resin in the fiberglass and core material layer and the side of the product gel coat layer away from the mold. This results in the formation of an integrated composite material structure of the anti-slip strip gel coat layer, the anti-slip particle layer, the product gel coat layer, and the fiberglass and core material layer, yielding a semi-finished cabin cover. The semi-finished cabin cover is removed from the mold, so that the exposed ends of the multiple anti-slip particles form a particle exposed surface that is not continuously covered by the anti-slip strip gel coat layer, and together with the anti-slip strip gel coat layer, they form an anti-slip surface.
[0009] Furthermore, when laying the anti-slip particles on the surface of the anti-slip tape gel coat layer, the anti-slip particles are loaded into a screen-type spreader and evenly spread on the surface of the anti-slip tape gel coat layer. The anti-slip particles do not overlap each other or form multiple layers, and gaps are maintained between adjacent anti-slip particles to allow the product gel coat to enter. After the spreading is completed, a compaction tool is used to apply a compaction force evenly to the anti-slip particles from the anchoring end side; The compaction tool has an elastic compaction surface on one side facing the anti-slip particles, and the elastic compaction surface fits the anchoring end of different anti-slip particles.
[0010] Furthermore, when spraying the product gel coat onto the overall surface of the mold, multi-directional cross-spraying is used in the anti-slip strip area, so that the product gel coat enters from the anchoring end side of the anti-slip particles and enters between the anti-slip particles, covering the periphery of the anti-slip particles near the anchoring end and the anchoring end, and filling the gaps between adjacent anti-slip particles near the anchoring end, so that the product gel coat layer forms a continuous covering structure on the anchoring end side of the anti-slip particles.
[0011] Furthermore, when the glass fiber material and the core material are sequentially laid on the surface of the product gel coat layer, chopped strand mat, composite mat, core material and core mat are sequentially laid on the side of the product gel coat layer away from the mold. The chopped strand mat adheres to the undulating surface formed by the product gel coat layer on one side of the anchoring end of the anti-slip particle, and adheres to the surface recesses formed by the product gel coat layer between adjacent anti-slip particles.
[0012] Furthermore, a vacuum infusion process is used for curing and molding, and the resin is a liquid resin; On the side of the glass fiber and sandwich material layer away from the mold, a release cloth and a flow guide net are laid in sequence, and a resin feeding pipeline and a vacuum extraction pipeline are arranged. The forming area of the mold is covered with a vacuum bag film, and the vacuum bag film is continuously sealed to the mold with a sealing strip to form a closed cavity; The release cloth, the flow guide net, the vacuum bag film, the resin feeding pipeline, and the vacuum extraction pipeline together constitute the vacuum auxiliary material layer; A vacuum pump is connected to the vacuum extraction pipeline to evacuate the sealed cavity, and the liquid resin is introduced to impregnate the glass fiber material.
[0013] Furthermore, the anti-slip gelcoat, the product gelcoat, and the liquid resin are a mutually compatible material system suitable for continuous coating in a surface-dry state; The liquid resin is an unsaturated polyester resin, epoxy resin, or vinyl ester resin; The liquid resin flows under negative pressure, impregnates the glass fiber material, and reaches the side of the product gel coat layer away from the mold through the fiber gaps of the glass fiber material.
[0014] Furthermore, hand lay-up molding is employed, in which the glass fiber material and the core material are sequentially laid on the surface of the gel coat layer of the product. During the laying of the glass fiber material, the resin is applied in layers and rolled to remove air, so that the resin impregnates the glass fiber material, and then it is cured and molded.
[0015] Furthermore, compression molding is employed, in which the glass fiber material and the core material are laid on the surface of the gel coat layer of the product. After the mold is closed, molding pressure is applied to impregnate the glass fiber material with the resin and maintain this state until the resin cures.
[0016] This invention provides an integrally molded anti-slip strip for a wind turbine nacelle and its manufacturing method, which has the following beneficial effects: 1. This invention embeds anti-slip particles between the gel coat layer of the anti-slip tape and the gel coat layer of the product, and then co-cures them with resin to form an integrated composite material structure. This achieves double gel coat coating and anchoring of the anti-slip particles and deep bonding of the materials. Compared with the traditional sand-sprinkling process where anti-slip particles are only attached to the surface gel coat after molding, this invention improves the bonding strength of the anti-slip layer, avoids the problem of falling off under long-term outdoor temperature difference cycles and personnel trampling conditions, and extends the service life of the anti-slip tape.
[0017] 2. This invention precisely defines the anti-slip zone area by directly machining grooves of a specific depth on the surface of the main mold. Combined with a screen-type spreader to quantitatively lay a single layer of anti-slip particles and standardized pressing control, it achieves that the sharp corners or edges of the anti-slip particles are naturally exposed and the exposure degree is consistent after demolding. Compared with the traditional manual sand spreading process, it avoids the defects of uneven particle distribution and difficulty in controlling thickness caused by manual operation, ensuring the uniformity and stability of the anti-slip texture and making the friction coefficient of the product surface more controllable.
[0018] 3. This invention prefabricates the anti-slip strip structure in the mold groove and uses integrated molding to allow the anti-slip surface to naturally form as the product is demolded. This achieves synchronous processing of the anti-slip strip and the engine compartment cover body. Compared with the traditional process that requires secondary grinding and sanding after curing and the separate production and bonding of the anti-slip mold, this invention eliminates the cumbersome post-processing and mold bonding procedures. It avoids the problems of easy wear and fall-off of the additional mold and the impact of mold release agent residue on surface quality. This simplifies the process, reduces manufacturing costs, and improves the consistency of finished products and overall production efficiency in mass production. Attached Figure Description
[0019] Figure 1 This is a cross-sectional view of the integrated anti-slip strip for the wind turbine nacelle cover of the present invention. Figure 2 This is a flowchart of the manufacturing method of the integrated anti-slip strip for the wind turbine nacelle cover of the present invention; Figure 3 This is a flowchart illustrating the mold groove processing and surface treatment, anti-slip strip gel coat layer construction, and pressable embedding state determination of the present invention. Figure 4 This is a flowchart illustrating the process of laying and pressing the anti-slip granular layer and constructing the gel coat layer of the present invention. Figure 5 This is a flowchart illustrating the glass fiber and core material layer laying, vacuum infusion, and curing process of the present invention. Figure 6 This is a flowchart illustrating the process of removing auxiliary materials, demolding, and forming the anti-slip surface according to the present invention. Figure 7 This is a graph showing the trend of particle loss rate variation for two groups of samples under cyclic shear load in an embodiment of the present invention. Figure 8This is a bar chart comparing the friction coefficients of two groups of samples under dry and wet conditions in an embodiment of the present invention.
[0020] The components include: 1. Mold; 2. Anti-slip gel coat layer; 3. Anti-slip particle layer; 4. Product gel coat layer; 5. Fiberglass and sandwich material layer; and 6. Vacuum auxiliary material layer. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] See attached document Figure 1 The present invention provides an integrally molded anti-slip strip for a wind turbine nacelle cover, comprising an anti-slip strip gel coat layer 2, an anti-slip particle layer 3, a product gel coat layer 4, and a glass fiber and core material layer 5.
[0023] The anti-slip strip gelcoat layer 2 forms the outer surface gelcoat substrate of the anti-slip strip area. The anti-slip particle layer 3 consists of multiple anti-slip particles spaced apart and is disposed between the anti-slip strip gelcoat layer 2 and the product gelcoat layer 4. The product gelcoat layer 4 is disposed on the side of the anti-slip particle layer 3 facing away from the mold 1. The fiberglass and core material layer 5 is disposed on the side of the product gelcoat layer 4 facing away from the anti-slip particle layer 3. For ease of explanation, the following uses the directional relationship between the anti-slip particles and the mold 1 during the molding process as a reference. The end of the anti-slip particle facing the mold 1 and in contact with the bottom surface of the groove of the mold 1 is called the exposed end, and the end of the anti-slip particle facing away from the mold 1 is called the anchoring end.
[0024] During molding, the exposed ends of multiple anti-slip particles in the anti-slip particle layer 3 pass through the anti-slip gel coat layer 2 and contact the bottom surface of the groove in the mold 1. The anti-slip gel coat layer 2 covers the periphery of the anti-slip particles near the exposed ends, and the product gel coat layer 4 covers the periphery of the anti-slip particles near the anchoring ends and the anchoring ends. The side of the product gel coat layer 4 facing away from the mold 1 forms an interface with the cured resin in the fiberglass and core material layer 5, making the anti-slip gel coat layer 2, anti-slip particle layer 3, product gel coat layer 4, and fiberglass and core material layer 5 an integral structure. After demolding, the exposed ends of multiple anti-slip particles are exposed on the outer surface of the cabin cover and together with the anti-slip gel coat layer 2, form an anti-slip surface.
[0025] See attached document Figure 2 This invention provides a method for manufacturing an integrally formed anti-slip strip for a wind turbine nacelle. In this embodiment, taking vacuum injection process as an example, the method includes the following steps: S1, process grooves on the surface of mold 1, clean the surface of mold 1 and apply release agent; S2, spray anti-slip tape gel coat into the groove of mold 1, and let it stand until it is surface dry and not completely cured, forming anti-slip tape gel coat layer 2. S3, lay anti-slip particles on the surface of the anti-slip strip gel coat layer 2, and press the exposed ends of multiple anti-slip particles laid in the anti-slip strip area into the anti-slip strip gel coat layer 2 until they contact the bottom surface of the groove of the mold 1 to form an anti-slip particle layer 3. S4, spray the product gel coat onto the entire surface of mold 1, so that the product gel coat covers the periphery of the anti-slip particles near the anchor end and the anchor end, and fills the gap between adjacent anti-slip particles near the anchor end, and let it stand until it is surface dry to form product gel coat layer 4. S5, glass fiber material and core material are sequentially laid on the surface of the product gel coat layer 4 to form glass fiber and core material layer 5; S6, a vacuum auxiliary material layer 6 is arranged on the outside of the glass fiber and sandwich material layer 5, the forming area of the mold 1 is sealed and vacuumed, liquid resin is introduced, so that the liquid resin wets the glass fiber material in the glass fiber and sandwich material layer 5, and then curing is performed, so that the cured resin in the glass fiber and sandwich material layer 5 forms an interface bond with the side of the product gel coat layer 4 away from the mold 1. S7, remove the vacuum auxiliary material layer 6, remove the semi-finished engine cover from the mold 1, so that the exposed ends of multiple anti-slip particles in the anti-slip particle layer 3 are exposed and form an anti-slip surface.
[0026] The following section explains the specific implementation process of each of the above steps.
[0027] See attached document Figure 3 For step S1, the specific sub-steps are as follows: S101, define the anti-slip strip area on the surface of mold 1, and process grooves within the anti-slip strip area.
[0028] Based on the engineering drawings of the nacelle cover product, the boundary of the anti-slip strip area is determined on the working surface of mold 1, and a groove is machined within this area. The length and width of the groove are determined according to the design dimensions of the anti-slip strip area; in this embodiment, the groove depth is 1 mm.
[0029] The groove in mold 1 is used to define the boundary of the anti-slip strip area and to provide molding space for the anti-slip strip gel coat and anti-slip particles.
[0030] S102, Clean mold 1 and apply release agent.
[0031] Clean the working surface of mold 1, as well as the bottom and side walls of the groove, with a special cleaning agent to remove dust, debris, and oil generated during processing. After the special cleaning agent has evaporated and the surface of mold 1 is dry, apply a release agent evenly to the working surface of mold 1, as well as the bottom and side walls of the groove, to prevent the release agent from accumulating locally in the groove, so as not to affect the contact between the anti-slip particles and the bottom surface of the groove.
[0032] For cleaning and demolding of the surface of mold 1, those skilled in the art can use cleaning agents, release waxes or semi-permanent liquid release agents commonly used in composite material molding. The material selection and coating process are well-known technologies in the field and will not be described in detail here.
[0033] Step S2 specifically includes the following sub-steps: S201, spray anti-slip gel coat into the groove of mold 1.
[0034] Using the groove boundary of mold 1 as the spraying boundary, the anti-slip gelcoat is evenly sprayed onto the bottom and sidewalls of the groove. The anti-slip gelcoat uses a different color from other areas of the cabin cover to make the formed anti-slip area identifiable. In this embodiment, the wet film thickness of the anti-slip gelcoat is 0.5–0.7 mm.
[0035] During the spraying process, by controlling the number of spray passes and the speed of the spray gun movement, the anti-slip gel coat is made to form a continuous film layer in the groove, and local accumulation is avoided.
[0036] S202, so that the anti-slip tape gel coat layer 2 reaches a pressable state that is surface dry but not yet fully cured.
[0037] After the anti-slip gelcoat is applied, allow it to stand for 1.5 to 3 hours at 20–40℃. The specific standing time depends on the ambient temperature and the curing characteristics of the anti-slip gelcoat. During formal construction, a process witnessing area is simultaneously set up in the non-product area of mold 1 or on an independent witnessing board. The process witnessing area has a witnessing groove with the same groove depth as mold 1, and construction and standing are carried out using the same batch of anti-slip gelcoat, the same wet film thickness of the anti-slip gelcoat, and the same environmental conditions. The press-fit state means that the anti-slip gelcoat layer 2 has gelled, no longer flows, and can maintain the spray thickness. Its surface reaches a surface-dry state where it is not sticky to the touch, but the anti-slip gelcoat layer 2 has not been fully cured. Using anti-slip particles of the same sieve and grade as those used in formal construction, and a compaction tool with the same compaction tool and elastic compaction surface condition as those used in the independent pre-calibrated test, an immediate press-fit test is conducted in the process witnessing area.
[0038] The anti-slip granules are compacted according to the calibrated pressing stroke determined by independent pre-calibrated samples before formal production. If the compaction tool reaches the calibrated pressing stroke, and the anti-slip granules remain pressed in without significant rebound after the tool is removed, and the anti-slip gel coat layer 2 does not crack, peel, or flow as a whole, then the anti-slip gel coat layer 2 is considered to have reached the compressible state and proceeds to step S3. If the anti-slip gel coat layer 2 has not yet reached the surface dry state, or if it flows as a whole during pressing, it is allowed to stand for a while and then re-evaluated. If the anti-slip gel coat layer 2 has reached the surface dry state but the compaction tool cannot reach the calibrated pressing stroke, or if the anti-slip gel coat layer 2 has completely cured and cracks or peels during pressing, this batch does not proceed to step S3.
[0039] See attached document Figure 4 For step S3, the specific sub-steps are as follows: S301, select anti-slip particles and control the size matching relationship.
[0040] The anti-slip particles are made of quartz sand. For any anti-slip particle after being screened by the selected sieve, the particle size characterized by the sieve classification is called the equivalent particle size. In this embodiment, the equivalent particle size of the selected anti-slip particles is 3-5 mm; For any anti-slip particle in the selected sieve gradation, the equivalent particle size of the anti-slip particle is greater than the groove depth of mold 1, and the equivalent particle size of the anti-slip particle is greater than the sum of the wet film thickness of the anti-slip gelcoat and the wet film thickness of the product gelcoat.
[0041] The equivalent particle size of the anti-slip particles is greater than the groove depth of mold 1. This serves as the selection relationship between the anti-slip particles and the groove depth of mold 1, providing a dimensional basis for ensuring that the exposed end of the anti-slip particles contacts the bottom surface of the groove in mold 1 and the anchoring end is located outside the groove after compaction. The equivalent particle size of the anti-slip particles is greater than the sum of the wet film thickness of the anti-slip tape gelcoat and the wet film thickness of the product gelcoat. This serves as an auxiliary selection relationship between the anti-slip particles and the nominal wet film thickness of the two layers of gelcoat, allowing for dimensional margins to be provided for gelcoat coverage of the periphery and anchoring end of the anti-slip particles. Since the anti-slip particles are irregular particles, the above dimensional relationships do not necessarily guarantee that the anti-slip particles will be exposed. The exposure state of the anti-slip particles also depends on the actual shape, laying posture, and pressing state of the anti-slip particles. In this embodiment, the maximum value of the sum of the wet film thickness of the anti-slip tape gelcoat and the wet film thickness of the product gelcoat is 1.4 mm, and the minimum value of the equivalent particle size of the selected anti-slip particles is 3 mm. The selected parameters satisfy the above auxiliary selection relationships.
[0042] The anti-slip particles can also be made of corundum sand, silicon carbide particles, or ceramic particles. Their equivalent particle size can be adjusted according to the anti-slip requirements while satisfying the aforementioned dimensional matching relationship. For the quartz sand used in this embodiment, within an overall particle size range of 3–5 mm, one relatively concentrated sieve distribution is selected for the same construction batch to reduce the particle size difference between anti-slip particles. When using corundum sand, silicon carbide particles, or ceramic particles, a relatively concentrated sieve distribution is selected within the particle size range that satisfies the aforementioned dimensional matching relationship. The anti-slip particles should be kept dry before use, and particles that do not conform to the selected sieve distribution should be sieved out.
[0043] S302, lay and press in anti-slip granules.
[0044] The anti-slip granules are loaded into a screen-type spreader and evenly spread on the surface of the gel coat layer 2 of the anti-slip tape. In this embodiment, the laying density of the anti-slip granules is 1 kg / m². 2 .
[0045] The anti-slip particles are evenly distributed in the planar distribution range and basically cover the entire anti-slip strip area, maintaining a single-layer laying state in the thickness direction; gaps are reserved between adjacent anti-slip particles to allow the product gel coat to enter, and the anti-slip particles do not overlap each other or form multiple layers of accumulation.
[0046] After the application is completed, a compaction tool that does not stick to the anti-slip strip gel coat is used to apply a uniform compaction force to the anti-slip particles from the anchoring end side, so that the exposed ends of multiple anti-slip particles laid in the anti-slip strip area pass through the anti-slip strip gel coat layer 2 and contact the bottom surface of the groove of the mold 1.
[0047] In this embodiment, an elastic compaction surface is provided on the side of the compaction tool facing the anti-slip particles. This surface can individually conform to the anchoring ends of different anti-slip particles to accommodate differences in particle size and laying posture within the same sieve gradation. The elastic compaction surface is made of an elastic material that does not adhere to the gel coat of the anti-slip tape, and its material, thickness, and hardness remain consistent during independent pre-calibration and formal construction. The elastic deformation of the compaction surface during compaction is included within the calibrated pressing stroke. This calibrated pressing stroke is used to reproduce the compaction state confirmed by the independently pre-calibrated sample and is not directly used as the calculated value of the actual compaction depth of the anti-slip particles.
[0048] Before formal production, independent pre-calibration samples were prepared using the same groove depth, anti-slip tape gelcoat, product gelcoat, wet film thickness of the anti-slip tape gelcoat, wet film thickness of the product gelcoat, anti-slip particle sieving and distribution, compaction tools, and environmental conditions as in formal construction. Multiple mutually separated and structurally identical calibration areas were set up on the independent pre-calibration samples, with each calibration area using the same anti-slip particle laying density and laying method.
[0049] After the anti-slip tape gel coat reaches the pressable state, the anti-slip particles are compacted using different downward strokes in different calibration areas. Only one compaction operation is performed in the same calibration area, and the starting position of the downward stroke is the position where the elastic compaction surface begins to contact the anchor end of the anti-slip particle. After the independent pre-calibrated sample completes the product gel coat construction and curing, it is demolded as a whole, and multiple interval positions are selected in each calibration area to form a cross section.
[0050] For any calibration area, the observation results of each profile within that calibration area are considered. When the exposed ends of multiple anti-slip particles reach the outer surface of the sample and form a particle exposure surface not continuously covered by the anti-slip tape gel coat layer 2, the anchoring ends of the anti-slip particles are covered by the product gel coat, and there is no obvious cracking or peeling of the anti-slip tape gel coat layer 2, the pressing stroke corresponding to that calibration area is determined to meet the pressing requirements. In each calibration area that meets the pressing requirements, the corresponding minimum pressing stroke is determined as the calibration pressing stroke, and the calibration pressing stroke and the corresponding compaction tool status are recorded in the process record.
[0051] During formal construction, after confirming in the process witnessing area that the anti-slip tape gelcoat layer 2 has reached a pressable state, the anti-slip particles are compacted according to the calibrated pressing stroke. The pressing stroke must be recalibrated if there are any changes to the anti-slip tape gelcoat, product gelcoat, the wet film thickness of any gelcoat, the sieve distribution of the anti-slip particles, the compaction tools, or environmental conditions. The pressing stroke must also be recalibrated if the elastic compaction surface is replaced, shows significant wear, or undergoes permanent deformation.
[0052] During the pressing process, the anti-slip particles should be evenly distributed within the anti-slip zone to prevent lateral movement, aggregation, or tipping of the particles. The exposed ends of multiple anti-slip particles that contact the bottom surface of the groove in mold 1 correspond to the parts of the anti-slip particles that are exposed on the outer surface of the semi-finished engine compartment cover after demolding.
[0053] Step S4 specifically includes the following sub-steps: S401, spray product gel coat onto the entire surface of mold 1.
[0054] After the anti-slip particle layer 3 is laid, product gelcoat is sprayed onto the entire working surface of mold 1, covering both the non-anti-slip and anti-slip areas. In the anti-slip area, multi-directional cross-spraying is used, allowing the product gelcoat to enter between the anti-slip particles from the anchoring end side, covering the periphery and anchoring end of the anti-slip particles, and filling the gaps between adjacent anti-slip particles near the anchoring end. This creates a continuous coating structure of product gelcoat layer 4 on the anchoring end side of the anti-slip particles. During spraying, the spraying direction, pressure, and amount of product gelcoat are controlled to maintain the stable position of the anti-slip particles and avoid forming obvious product gelcoat layers between the exposed ends of the anti-slip particles and the bottom surface of the groove in mold 1.
[0055] S402, control the wet film thickness of the product gel coat and let it stand until it is surface dry.
[0056] The wet film thickness of the product gelcoat measured on the flat working surface of mold 1 where anti-slip particles are not laid is 0.5–0.7 mm. For the anti-slip strip area, the product gelcoat is considered to continuously cover the periphery and anchor end of the anti-slip particles near the anchor end, fill the gap between adjacent anti-slip particles near the anchor end, and there is no obvious missed coating or local accumulation that would affect subsequent layup.
[0057] After spraying, allow the product to stand at 20–40℃ for 1.5–3 hours. The specific standing time depends on the ambient temperature and the curing characteristics of the product's gel coat, until the product's gel coat layer 4 reaches a surface-dry state where it is no longer sticky to the touch. Once surface-dry, the product's gel coat layer 4 should be able to withstand the subsequent laying of the glass fiber and core material layer 5, and the position of the anti-slip particles should remain stable.
[0058] See attached document Figure 5 For step S5, the specific sub-steps are as follows: S501, fiberglass material and core material are laid on the surface of the gel coat layer 4 of the product.
[0059] After the product gel coat layer 4 reaches a surface dry state, according to the set layup scheme, chopped strand mat, composite mat, core material, and sandwich mat are sequentially laid on the side of the product gel coat layer 4 away from the mold 1 to form a glass fiber and sandwich material layer 5. Chopped strand mat is laid first in the anti-slip zone area, ensuring it adheres to the undulating surface formed by the product gel coat layer 4 on the anchoring end of the anti-slip particles and to the surface depressions formed between adjacent anti-slip particles. During the laying process, the position of the anti-slip particles is kept stable to avoid significant bridging or unbonded areas around the anti-slip particles caused by the chopped strand mat. Subsequently, composite mat, core material, and sandwich mat are laid sequentially.
[0060] For the layup design of the glass fiber and sandwich material layer 5, those skilled in the art can determine the material type, number of layers and layup direction according to the load requirements of the cabin cover. The layup design is a well-known technology in the field and will not be described in detail here.
[0061] Step S6 specifically includes the following sub-steps: S601, arrange the vacuum auxiliary material layer 6 and seal the mold 1.
[0062] On the side of the glass fiber and sandwich material layer 5 facing away from the mold 1, a release cloth and a flow guide net are laid in sequence, and resin feeding pipes and vacuum extraction pipes are arranged. A vacuum bag film is used to cover the molding area of the mold 1, and the vacuum bag film is continuously sealed to the mold 1 by a sealing strip, so that a closed cavity is formed between the vacuum bag film and the mold 1. The release cloth, flow guide net, vacuum bag film, and corresponding pipes together constitute the vacuum auxiliary material layer 6.
[0063] Regarding the arrangement of the vacuum auxiliary material layer 6 and the design of the resin flow channel, those skilled in the art can determine the position of the resin feed pipeline, vacuum pumping pipeline and flow guide net according to the size of the mold 1 and the layup structure. The arrangement and design are well-known technologies in the field and will not be described in detail here.
[0064] S602, evacuate and perform pressure testing for leaks.
[0065] A vacuum pump is connected via a vacuum evacuation line to evacuate the sealed cavity. The gauge pressure inside the sealed cavity is controlled at -0.08 MPa or below.
[0066] Once the gauge pressure inside the sealed cavity reaches the above requirements, close the corresponding valves and maintain the pressure for 5 minutes. If the gauge pressure does not continue to rise during the pressure maintenance period, confirm that the sealed cavity meets the resin filling requirements; if the gauge pressure continues to rise, check the vacuum bag membrane and sealing strip for leaks and reseal them.
[0067] S603, introduces liquid resin and cures it into shape.
[0068] After confirming that the sealed cavity meets the resin injection requirements, the resin inlet valve is opened, and unsaturated polyester resin is introduced. The anti-slip strip gelcoat, product gelcoat, and unsaturated polyester resin are a material system that has been confirmed by the material process documents to be compatible with each other and suitable for continuous coating in a surface-dry state. Under negative pressure, the liquid resin flows along the guide net, wetting the glass fiber material in the anti-slip strip area and non-anti-slip strip area, and spreading along the surface of the core material. The liquid resin reaches the side of the product gelcoat layer 4 away from the mold 1 through the fiber gaps of the glass fiber material.
[0069] When the resin flow front reaches the area of the vacuum extraction pipeline, and both the anti-slip zone and non-anti-slip zone areas are impregnated with resin without obvious dry spots, the resin introduction is considered complete. Close the resin inlet valve and maintain the sealed cavity under negative pressure. Curing time is 6 hours at 20–40°C. During the curing process, a resin witness sample using the same batch of resin and under the same environmental conditions as the semi-finished engine room cover is provided.
[0070] After 6 hours of curing, the demolding index specified in the resin material process document is used to determine whether the semi-finished engine room cover has met the demolding conditions, based on the curing status of the resin witness sample. If the demolding conditions have not yet been met, curing continues until they are met. During the curing process, the resin impregnating the glass fiber material forms an interface bond with the product gel coat layer 4, causing the anti-slip tape gel coat layer 2, the anti-slip particle layer 3, the product gel coat layer 4, and the glass fiber and core material layer 5 to form an integrated composite material structure.
[0071] In other embodiments, the unsaturated polyester resin can be replaced with epoxy resin or vinyl ester resin, and correspondingly selected anti-slip tape gelcoat and product gelcoat that are compatible with epoxy resin or vinyl ester resin and suitable for continuous coating are selected. The curing temperature and curing time are determined according to the curing characteristics of the resin system used.
[0072] The above steps S601 to S603 are illustrated using vacuum infusion as an example. In other embodiments, hand lay-up molding or compression molding can be used instead of the vacuum infusion and curing molding process in step S6, depending on the production conditions.
[0073] When using hand lay-up molding, glass fiber material and core material are sequentially laid on the surface of the product's gel coat layer 4. During the laying of the glass fiber material, resin is applied in layers and roll-pressed to remove air, allowing the glass fiber material to be impregnated with resin. Then, curing is performed according to the curing conditions of the resin system used. When using compression molding, glass fiber material and core material are laid on the surface of the product's gel coat layer 4. After mold closing, molding pressure is applied to impregnate the glass fiber material with resin and maintain this pressure until the resin cures. In both hand lay-up molding and compression molding, the cured resin in the glass fiber and core material layers 5 forms an interface bond with the side of the product's gel coat layer 4 facing away from the mold 1. Neither of these alternative processes uses a vacuum auxiliary material layer 6, and the relative positions of the anti-slip gel coat layer 2, anti-slip particle layer 3, product gel coat layer 4, and glass fiber and core material layer 5 remain unchanged during the laying, mold closing, and curing processes.
[0074] See attached document Figure 6 For step S7, the specific sub-steps are as follows: S701, Remove the vacuum auxiliary material layer 6 and remove the semi-finished engine cover from the mold 1.
[0075] After confirming that the semi-finished nacelle cover meets the demolding conditions according to the demolding indicators specified in the resin material process documents and the curing state of the resin witness sample, remove the seal around mold 1, and then remove the vacuum bag film, guide net, and demolding cloth in sequence. Subsequently, gradually apply demolding force along the edge of mold 1 to separate the semi-finished nacelle cover from mold 1. During demolding, avoid applying concentrated prying force directly to the anti-slip strip area to reduce the loosening of anti-slip particles or damage to the anti-slip strip gel coat layer 2. When using hand lay-up molding or compression molding, remove the molding auxiliary materials according to the corresponding molding process after curing, and then remove the semi-finished nacelle cover from mold 1.
[0076] S702, expose the exposed ends of multiple anti-slip particles in the anti-slip particle layer 3 and perform post-processing.
[0077] After the semi-finished nacelle cover is removed from mold 1, the exposed ends of multiple anti-slip particles that contacted the bottom surface of the groove in mold 1 during the molding process form a particle exposed surface that is not continuously covered by the anti-slip gel coat layer 2, and is directly exposed on the outer surface of the semi-finished nacelle cover. The particle exposed surface and the anti-slip gel coat layer 2 together form an anti-slip surface, and the particle surfaces, sharp corners, or edges of the exposed ends of the multiple anti-slip particles create a granular, rough anti-slip texture on the anti-slip surface.
[0078] After demolding, the semi-finished nacelle cover is trimmed, punched, and finished. The anti-slip surface is already formed during demolding, so there is no need to grind the anti-slip area or apply anti-slip particles a second time, thus obtaining a finished nacelle cover with an integrally formed anti-slip strip.
[0079] Specific application examples: The following describes the specific application of this invention, using the manufacturing process of a 6MW offshore wind turbine nacelle cover and the test results of the corresponding samples. The samples for this application example were prepared according to the aforementioned steps S1 to S7.
[0080] The groove depth of the anti-slip strip area in mold 1 is set to 1.0 mm, the wet film thickness of the anti-slip strip gelcoat is 0.6 mm, and the wet film thickness of the product gelcoat is 0.5 mm. Based on these parameters, the equivalent particle size of the selected anti-slip particles is greater than the groove depth of mold 1 and greater than the sum of the nominal wet film thicknesses of the anti-slip strip gelcoat and the product gelcoat.
[0081] In this application example, quartz sand is selected as the anti-slip particles, and the equivalent particle size of the selected anti-slip particles is 3.0 to 3.5 mm by sieving.
[0082] The anti-slip particles in the same construction batch are sized using the above-mentioned sieve classification. The equivalent particle size of any anti-slip particle in the selected sieve classification is greater than the groove depth of mold 1 and greater than the sum of the nominal wet film thickness of the anti-slip tape gelcoat and the product gelcoat, satisfying the aforementioned size selection relationship.
[0083] The anti-slip tape gelcoat, product gelcoat, and unsaturated polyester resin are selected as a compatible material system suitable for continuous coating in a surface-dry state. The anti-slip tape gelcoat and product gelcoat are left to stand at 20–40°C for 1.5–3 hours, and the timing of subsequent construction is determined according to the conditions specified in steps S202 and S402. The elastic compaction surface of the compaction tool is made of a material that does not adhere to the anti-slip tape gelcoat and can elastically recover; its material, thickness, and hardness remain consistent during independent pre-calibration and formal construction. Before formal production, independent pre-calibration samples are prepared according to step S302, and the pressing stroke corresponding to different calibration areas is judged to meet the pressing requirements; only the minimum pressing stroke that allows multiple anti-slip particles to form a visible particle surface, the anchoring end of the anti-slip particles to be covered by the product gelcoat, and the anti-slip tape gelcoat layer 2 to show no obvious cracking or peeling is determined as the calibration pressing stroke.
[0084] During formal construction, after confirming in the process witnessing area that the anti-slip tape gel coat layer 2 has reached a pressable state, the anti-slip particles are compacted according to the calibrated pressing stroke, so that the exposed ends of multiple anti-slip particles contact the bottom surface of the groove in mold 1, and the anchoring ends of the anti-slip particles are left on the side of the anti-slip tape gel coat layer 2 away from mold 1, for product gel coat coating. After the glass fiber and core material layer 5 are laid, the gauge pressure in the closed cavity is controlled at -0.08MPa or below, and the pressure is maintained for 5 minutes to confirm that the closed cavity meets the resin injection requirements. Then, unsaturated polyester resin is introduced and cured at 20-40℃ for 6 hours. If the demolding conditions have not been met after 6 hours of curing, curing continues until the demolding conditions are met.
[0085] Meanwhile, the anti-slip strip of the engine hood prepared using the post-molding sand-spreading process was selected as a comparative sample, and its performance was compared with that of the sample prepared using the aforementioned one-piece molding process. The post-molding sand-spreading process refers to the process of surface treatment of the anti-slip strip area after the engine hood has been cured and molded, applying a gel coat, and then spreading anti-slip particles before the gel coat cures.
[0086] See attached document Figure 7 To ensure that the test results primarily reflect the differences in the bonding structure of the anti-slip particles, the comparative sample and the sample in this application example used anti-slip particles with the same material and sieve distribution. Areas with comparable distribution and surface exposure of the anti-slip particles before the test were selected as the test area and statistical area of the anti-slip strip.
[0087] During the experiment, both groups of samples used the same sample size and anti-slip strip test area, and under the same normal pressure, reciprocating stroke, and reciprocating frequency, they were subjected to reciprocating shear friction using a reciprocating abrasion testing machine. Both groups of samples used friction heads of the same material and size, and the environmental conditions and sample fixing methods were kept consistent. Every 1000 cycles, the particle loss rate on the sample surface was recorded using the same statistical method within the same statistical area. A comparison was made between the same statistical area before and after the test; exposed anti-slip particles that were identifiable before the test but no longer present at the corresponding location after the test were counted as detached anti-slip particles. The particle loss rate was determined as the percentage of detached anti-slip particles relative to the total number of identifiable exposed anti-slip particles in the statistical area before the test.
[0088] like Figure 7 As shown, the particle loss rate of the comparative sample increased to 4.5% after 1000 cycles and reached 18.2% at the end of 5000 cycles. Observation of the surface of the comparative sample revealed that the particle bonding interface formed by the sand-spreading process after molding exhibited local peeling under alternating stress. In contrast, the particle loss rate test curve of the sample in this application embodiment maintained a gradual increase, and the particle loss rate was controlled below 1.3% after 5000 cycles.
[0089] In this application embodiment, the anchoring end of the anti-slip particles and the periphery near the anchoring end are continuously covered by the product gel coat layer 4. The side of the product gel coat layer 4 facing away from the mold 1 forms an interface bond with the cured resin in the glass fiber and core material layer 5, thereby making the anti-slip particle layer 3 and the glass fiber and core material layer 5 form an integral structure. Under the above sample preparation and testing conditions, the sample of this application embodiment has a low particle loss rate and good particle peel resistance stability under cyclic shear friction.
[0090] To address the issue of the top of the nacelle being susceptible to condensation or rain, the surface friction coefficient under wet conditions was further tested.
[0091] See attached document Figure 8 The two groups of samples used the same sample size, test direction and test area. The experiment used a pendulum friction coefficient measuring instrument to test the surface friction coefficient of the two groups of samples under the conditions of surface dryness and spraying deionized water to simulate rain.
[0092] During wet testing, both groups of samples were sprayed with the same amount of deionized water, within the same spray range, and with the same interval between spray completion and test start. Each sample was tested at the same location with the same number of repetitions, and the same data processing method was used to determine the surface friction coefficient. Test results showed that in a dry environment, the friction coefficient of the comparative sample was 0.78, while that of the sample in this application example was 0.86. After simulating a wet environment, the friction coefficient of the comparative sample decreased to 0.52, while the wet friction coefficient of the sample in this application example remained at 0.75. Surface observation of the comparative sample showed that the gel coat formed a high degree of coverage on the periphery of some anti-slip particles, reducing the exposure of the particle surface, sharp corners, or edges of the corresponding anti-slip particles.
[0093] This application embodiment, through the selection of anti-slip particle size, sieving and grading, and press-in control, ensures that the exposed ends of multiple anti-slip particles form particle surfaces that are not continuously covered by the anti-slip gel coat layer 2 after demolding. The particle surfaces, sharp corners, or edges of the exposed anti-slip particles, together with the anti-slip gel coat layer 2, form a granular, rough anti-slip texture. Therefore, the sample in this application embodiment maintains the corresponding surface friction properties under simulated wet conditions.
Claims
1. An integrally molded anti-slip strip for a wind turbine nacelle cover, characterized in that, It includes an anti-slip gel coat layer (2), an anti-slip particle layer (3), a product gel coat layer (4), and a glass fiber and core material layer (5). The anti-slip particle layer (3) is composed of a plurality of anti-slip particles spaced apart and is disposed between the anti-slip tape gel coat layer (2) and the product gel coat layer (4); The anti-slip particles have an exposed end and an anchoring end. The exposed end passes through the anti-slip tape gel coat layer (2) and forms a particle exposed surface that is not continuously covered by the anti-slip tape gel coat layer (2). The anti-slip tape gel coat layer (2) covers the periphery of the anti-slip particles near the exposed end. The product gel coat layer (4) covers the periphery of the anti-slip particles near the anchoring end and the anchoring end. The glass fiber and core material layer (5) is disposed on the side of the product gel coat layer (4) away from the anti-slip particle layer (3), and the side of the product gel coat layer (4) away from the anti-slip particle layer (3) forms an interface bond with the cured resin in the glass fiber and core material layer (5). The exposed surface of the particles together with the gel coat layer (2) of the anti-slip tape forms an anti-slip surface.
2. The one-piece molded anti-slip strip for a wind turbine nacelle cover according to claim 1, characterized in that, The exposed end of the anti-slip particles, the particle surface, sharp corners or edges, together with the anti-slip tape gel coat layer (2) form a granular rough anti-slip texture; the anti-slip particles are quartz sand, corundum sand, silicon carbide particles or ceramic particles.
3. A method for manufacturing an integrally molded anti-slip strip for a wind turbine nacelle cover, characterized in that, Manufacturing an integrally molded anti-slip strip for a wind turbine nacelle as described in any one of claims 1 or 2 includes the following steps: Define an anti-slip strip area on the surface of the mold (1), process a groove in the anti-slip strip area, clean the surface of the mold (1), and apply a release agent; Spray anti-slip gel coat into the groove of the mold (1), let it stand until it is surface dry and not completely cured, and form an anti-slip gel coat layer (2). Anti-slip particles are laid on the surface of the anti-slip tape gel coat layer (2). The end of the anti-slip particles facing the mold (1) is the exposed end, and the end of the anti-slip particles away from the mold (1) is the anchoring end. The exposed ends of multiple anti-slip particles are pressed into the anti-slip tape gel coat layer (2) until they contact the bottom surface of the groove to form an anti-slip particle layer (3). Spray product gel coat onto the entire surface of the mold (1) so that the product gel coat covers the periphery of the anti-slip particles near the anchor end and the anchor end, and fills the gap between adjacent anti-slip particles near the anchor end. Let it stand until it is surface dry to form a product gel coat layer (4). Glass fiber material and core material are laid on the surface of the product gel coat layer (4). During or after the glass fiber material is laid, resin is impregnated with the glass fiber material to form a glass fiber and core material layer (5). Then, it is cured and molded so that the cured resin in the glass fiber and core material layer (5) forms an interface with the side of the product gel coat layer (4) away from the mold (1), so that the anti-slip strip gel coat layer (2), the anti-slip particle layer (3), the product gel coat layer (4) and the glass fiber and core material layer (5) form an integrated composite material structure to obtain a cabin cover semi-finished product. The semi-finished cabin cover is removed from the mold (1), so that the exposed ends of the multiple anti-slip particles form a particle exposed surface that is not continuously covered by the anti-slip strip gel coat layer (2), and together with the anti-slip strip gel coat layer (2), they form an anti-slip surface.
4. The manufacturing method of an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, When laying the anti-slip particles on the surface of the anti-slip tape gel coat layer (2), the anti-slip particles are loaded into a screen-type spreader and evenly spread on the surface of the anti-slip tape gel coat layer (2). The anti-slip particles do not overlap each other or form multiple layers. A gap is left between adjacent anti-slip particles for the product gel coat to enter. After the spreading is completed, a compaction tool is used to apply a compaction force evenly to the anti-slip particles from the anchoring end side; The compaction tool has an elastic compaction surface on one side facing the anti-slip particles, and the elastic compaction surface fits the anchoring end of different anti-slip particles.
5. The manufacturing method of an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, When the product gel coat is sprayed onto the entire surface of the mold (1), multi-directional cross-spraying is used in the anti-slip strip area so that the product gel coat enters between the anti-slip particles from the anchoring end side of the anti-slip particles, covers the periphery of the anti-slip particles near the anchoring end and the anchoring end, and fills the gap between adjacent anti-slip particles near the anchoring end, so that the product gel coat layer (4) forms a continuous covering structure on the anchoring end side of the anti-slip particles.
6. The manufacturing method of an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, When the glass fiber material and the core material are laid sequentially on the surface of the product gel coat layer (4), chopped strand mat, composite mat, core material and core mat are laid sequentially on the side of the product gel coat layer (4) away from the mold (1); The chopped strand mat adheres to the undulating surface formed on the anchoring end side of the anti-slip particles by the product gel coat layer (4), and adheres to the surface recesses formed between adjacent anti-slip particles by the product gel coat layer (4).
7. The method for manufacturing an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, The resin is a liquid resin and is cured and molded using a vacuum infusion process. On the side of the glass fiber and sandwich material layer (5) away from the mold (1), a release cloth and a flow guide net are laid in sequence, and a resin feeding pipeline and a vacuum extraction pipeline are arranged. The forming area of the mold (1) is covered with a vacuum bag film, and the vacuum bag film and the mold (1) are continuously sealed with a sealing strip to form a closed cavity; The release cloth, the flow guide net, the vacuum bag film, the resin feeding pipeline and the vacuum extraction pipeline together constitute the vacuum auxiliary material layer (6). A vacuum pump is connected to the vacuum extraction pipeline to evacuate the sealed cavity, and the liquid resin is introduced to impregnate the glass fiber material.
8. The manufacturing method of an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 7, characterized in that, The anti-slip gelcoat, the product gelcoat, and the liquid resin are a mutually compatible material system suitable for continuous coating in a surface-dry state; The liquid resin is an unsaturated polyester resin, epoxy resin, or vinyl ester resin; The liquid resin flows under negative pressure, wets the glass fiber material, and reaches the side of the product gel coat layer (4) away from the mold (1) through the fiber gaps of the glass fiber material.
9. A method for manufacturing an integrally molded anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, Hand lay-up molding is used. The glass fiber material and the core material are laid sequentially on the surface of the gel coat layer (4) of the product. During the laying of the glass fiber material, the resin is applied in layers and the air is vented by rolling, so that the glass fiber material is impregnated by the resin. Then, it is cured and molded.
10. A method for manufacturing an integrally formed anti-slip strip for a wind turbine nacelle cover according to claim 3, characterized in that, The glass fiber material and the core material are laid on the surface of the gel coat layer (4) of the product by compression molding. After the mold is closed, molding pressure is applied to impregnate the glass fiber material with resin and hold it until the resin is cured.